Gestão ambiental no setor de construção civil de Aracaju - Santos, Augusto César Vieira dos (2006)
The sector of civil construction is one of impactantes, responsible mostly of the residues generated in the planet. The sped up growth of the cities comes causing ambient disequilibrium and reduction of the quality of life of population and one of the probable solutions is the implantation of sustainable cities, of echo-efficient constructions, stimulates it to the structure of the one productive chain of the sector with ecological principles, the use of alternative constructive and matter methods, or either, the search of the sustentabilidade of the sector. The companies are being pressured for the society to adopt measured of protection to the environment and social responsibility. So that the company takes decisions more possible adjust and can analyze the present situation of the company in relation to its customers, competitors and to the environment if make necessary the formularization of pointers. The use only of financial pointers, can generate a little real situation of that really the ideal is happening is, to use beyond the financial pointers, to get information of pointers of management, quality and ambient. For this study, we use as instrument of research, surveys in bibliographical sources and research effected in the area and study of case. Questionnaires had been applied that had served as exploratory instrument and of survey of questions, and had as objective, to evaluate the degree of importance of the ambient questions and quality in the companies of civil construction of Aracaju, as well as, of the practical ones of management come back to the environment. The research identified, among others questions, that in subtle way, the great concerns them studied companies had turned around the management of the quality and the strategical planning, and that for what we can observe, it did not include the variable ambient.